STRATEGI PENGEMBANGAN USAHA DALAM UPAYA MENINGKATKAN USAHA (Studi Pada Restoran Sop Saudara Jalan Ringroad Medan) - Andita Anastasia Saputri (Jurnal Niaga & Bisnis (e-journal), 2014)
This is done to determine the appropriate business development strategies for Sop Saudara Restaurant  in Jalan Ringroad Medan. Formulation of the problem in this study was to determine what internal factors into the strengths and weaknesses of Soup Restaurant brother, knowing what external factors into the opportunities and threats of Soup Restaurant brother, knowing how SWOT analysis on Sop Saudara Restaurant, and knowing how business development the Sop Saudara Restaurant. The method used is descriptive qualitative method. Data were obtained from observations, interviews and literature study. Analysis using SWOT analysis. Informants in this study amounted to 5 people. The use of informants using purposive sampling. The results show that the strategy needs to be applied to business development strategies Sop Saudara Restaurant is an aggressive strategy of creating a strategy that uses force to take advantage of opportunities. Keywords: Business Strategy, SWOT analysis